Risk Factors and Outcome of Pneumatosis Intestinalis in Children - Noha Heikal; Alessandra Mari; Jutta Köglmeier (Children)
Objectives: Pneumatosis intestinalis (PI) is rare in childhood. The aetiology remains poorly understood. Our aim was to assess its associated risk factors and outcome. Methods: Retrospective data collection of all children (>1 month of age) with radiological evidence of PI identified from 1991 to 2021 in a large children’s hospital. Poor outcome was defined as loss of enteral autonomy, or death within one month of PI diagnosis. Results: A total of 31 patients (21 male, 67.7%) were included, with a median age of 5 years. The underlying diagnosis was heterogenous. Cerebral palsy and acute lymphocytic leukaemia (ALL) were most common (5/31 for each, 16.13%). A share of 12/31 (38.7%) developed PI 2–15 months post-bone marrow transplantation (BMT). Most patients (n = 15, 48.4%) had no pre-existing gastroenterological disorder. In the majority (11/31, 35.5%), PI was an incidental finding. Abdominal pain was the most common presentation in symptomatic children (7/31, 22.6%). All (31/31, 100%) were managed conservatively with gut rest and antibiotics, and 6/31 (19.4%) had a poor outcome (1/31 permanent feeding intolerance, 5/31 died). When comparing patients who did well (group 1) to those with a poor outcome (group 2), worse prognosis was associated with a lower platelet count (p = 0.016), raised CRP (p = 0.008), higher creatinine (p = 0.006), and higher urea (p = 0.013). Conclusions: The overall prognosis of PI in childhood is good but associated with significant morbidity and mortality in a small number of patients. Our data suggest that lower platelet count, and higher urea, creatinine, and CRP levels might be risk factors.